EFEK PENGGUNAAN SIMVASTATIN TERHADAP KENAIKAN GULA DARAH PUASA PASIEN DIABETES MELITUS TIPE 2 - Yeni Farida; Claudia Putri (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2016)
Simvastatin were given in diabetes mellitus patient to reduce the risk of cardiovascular event.  Many studies have shown the effectiveness of statins in improving lipid profile. However, effects of statins on glucose metabolism are still unclear. The study aimed to investigate effect of simvastatin on increasing fasting plasma glucose.This retrospective cohort study using medical records included adult diabetes mellitus patient aged 18-60 years old that inpatient in 2014. We studied profil in fasting plasma glucose (FPG) in this population between before and after simvastatin therapy. Data were limited to patients who had 4 FPG measurements, 2 measurement before and 2 measurement at least a month after medication. Diagnosis of diabetes had to be present before the first FPG measurement.Coefficients kontingency analysis evaluated correlation between simvastatin and increasing of fasting plasma glucose.In this study, 15 patients were eligible. Before simvastatin therapy, 8 patients had normal level of FPG and 7 patients had abnormal level but it were decrease. After a month of simvastatin therapy, level of FPG had increased became abnormal in all patient.  Statin use is associated with a rise of FPG in patients with diabetes (p < 0.0001).